Enamel evaluation by scanning electron microscopy after debonding brackets and removal of adhesive remnants - Claudino, Dikson; Kuga, Milton-Carlos [UNESP]; Belizário, Lauriê [UNESP]; Pereira, Jefferson-Ricardo (Medicina Oral, S.L., 2018)
Background: The bonding of accessories in the dental crown during the orthodontic treatment creates microporosities, thus promoting micromechanical retention of the adhesive to the enamel structure. After debonding brackets, at the end of the active orthodontic treatment, a certain amount of adhesive remnants must be mechanically removed from the enamel. The objective of this study was to compare, by means of scanning electron microscopy, three different methods to remove the adhesive remnants after orthodontic bracket removal. Material and Methods: An experimental analytical study was conducted on human premolar specimens, extracted within a year or less. The preparation of the enamel was carried out with the application of 35% phosphoric acid and Transbond XT Light Cure Adhesive Primer® adhesive. Edgwise Standart prescription brackets, slot .022 (Morelli Orthodontia) were glued to the enamel using Transbond XT® bonding resin. The brackets were placed on the center of the vestibular face of the clinical crown, and a 300-gram pressure was exerted against the surface of the enamel, measured with an orthodontic dynamometer. The brackets were debonded with adhesive removing pliers, and the samples were divided into groups, according to the protocol used for adhesive remnant removal: high-speed multi-laminated drill bit, low-speed multi-laminated drill bit, and low-speed glass fiber. After removal of the adhesive remnants, the samples went through scanning electron microscopy, obtaining electro micrographs with a magnification range of 150 X, 500 X, and 2,000 X. Results: The tested method showed that the best effectiveness for the removal of the adhesive remnants after bracket debonding was the use of a tungsten carbide multi-laminated high speed, followed by the use of a tungsten carbide multi-laminated, low-rotation drill. The use of fiberglass drill alone has proved to be inefficient for clinical use, given the large amounts of adhesive remnants it leaves on the enamel Conclusions: All methods evaluated in this study proved to be inefficient for total removal of adhesive remnants from the enamel.
Keywords: Dental enamel; Microscopy; Orthodontics